actors Afifecting the Determin. a. tionRofAudit'bill Fee' s As Perce· 1 Ved b F External Auditors and Lun1ted espon~1 ty Companies y Working in Benghaz: Theoretical Analysis and Empirical Investigation - بكار محمود, د. مصطفى; مرعي الدرباق, أ. أمين (Dirasat in Economics and Business, 2004)
the purpose of this study is to investigate different factors affecting the determination of audit fes in benghazi as perceived by a sample of external auditors and private limited responsibolity companies a questionnaire was used a data collection method the answer of respondents show the internal control efficiency size the auditee and auditing difficulty and complexity are the main factors affacting audit fees